Sistema, fragmentación y contencioso internacional (Revista Española de Derecho Internacional, 2008)
It is submitted here that the theoretical framework on the discussion about the fragmentation of international law should be the concept of a legal system, where it would eventually appear its nature as a paradigmatic premise in the sense given by Th. S. Kuhn. The article considers, thus, some of the main approaches to law as a normative system in jurisprudence and in international law doctrine, pointing up their noteworthy evolution. Next it deals with the ambiguous meaning of a legal system underlying the ILC Report on the Fragmentation of international law issued in 2006, where it comes out a remarkable bias towards the formal structure of the legal system. This bias facilitates the conversion of fragmentation into a hermeneutic question that can be entirely solved by the correct application of the principle of systemic integration laid down in the Vienna Convention and the techniques of lex specialis, lex posterior and lex superior. This shift ends up in the affirmation of coherence as immanent while avoiding the problematic subject of the multiplication of international courts and tribunals. The article contends further that these two topics, namely fragmentation and proliferation of international judicial bodies, are intrinsically linked and, therefore, they can not be solved separately. As most theories show, the safeguard of a legal system’s coherence and unity depends on legal procedures that rely mainly on the existence of a proper judicial system. It is submitted that up to day there is no such judicial system in international law and the solutions suggested, such as the dialogue between judicial bodies, the judicial comity, the inherent powers to the judiciary or the unofficial authority of the International Court of Justice, are not fully convincing. Therefore, it seems difficult to ascertain the systemic nature of international law. Hence, the claim thereof shared by the international lawyers’ community is better described as a paradigmatic premise.